Sosialisasi Implementasi Kebijakan Mutu Untuk Peningkatan Kepuasan Pasien Di Rumah Sakit Grandmed Lubuk Pakam - Jon Piter Sinaga; Efrata Efrata; Novrika Silalahi; Ripai Siregar (INSTITUT KESEHATAN DELI HUSADA, 2021)
According to Article 1 of Law Number 14 of 2009, a hospital is a health service institution that provides complete individual health services that provide inpatient, outpatient, and emergency services. Health service is an effort made by the government together with the community in order to improve, maintain, and restore the health of the population which includes preventive, promotional, quantitative and rehabilitative services. In a narrow sense, these efforts are carried out by institutions that provide treatment to someone who is sick, in this case a hospital. Hospital services begin with a therapeutic transaction between doctors and patients. Patient satisfaction is very subjective, difficult to measure, can change, and there are many factors that influence as many dimensions as in human life. Subjectivism can be reduced and can even become objective if enough people have the same opinion on something. Therefore, to assess patient satisfaction, it is necessary to disseminate the implementation of the quality policy to all health workers who are in the health service.